Ο «θησαυρός» Πέλλα/2011. Παρατηρήσεις στη νομισματοκοπία των διοικητικο-πολιτικών ενοτήτων της Μακεδονίας του 2ου αι. π.Χ. - Ακαμάτης Νικόλαος (Tekmeria, 2022)
This article presents a small hoard of nine bronze coins that was discovered during excavations in room 29 of the east wing of the Agora of Pella, buried below a clay floor of the Hellenistic period. It contains one bronze coin in the name of the Amphaxians, three in the name of the Macedonians Amphaxians, four in the name of the Macedonians Botteatai, and one in the name of the Macedonians. Their description is the following (see p. 205, images 1-9): no. 1: Head of Herakles r. / Club, ΑΜΦΑ-ΞΙΩΝ, all in laurel wreath nos. 2-4: Head of Apollo r. / Tripod, ΜΑΚΕΔΟΝΩΝ (monogram: ΑΜΦ) nos. 5-8: Head of Zeus r. / Winged thunderbolt, ΜΑΚΕΔΟΝΩΝ (monogram: ΒΟΤ) no. 9: Head of Apollo r. / kithara, ΜΑΚΕΔΟΝΩΝ Both the dating and the circulation pattern of the bronze issues of the Amphaxians, the Botteatai and the Macedonians have been discussed extensively; it is now generally accepted that they were minted during the reign of the two last kings, Philip V and Perseus to serve for the needs of the local economies, but their issuing continued after the battle of Pydna and the control of Macedonia by the Romans. The iconography and the mintmarks of these coins can be connected to two other groups of bronze coins that were minted after 168 BC, namely the coins of the Roman quaestors in Macedonia and the autonomous coins of three major cities of the region, Thessaloniki, Pella and Amphipolis. The hoard from Pella is a rare case, because it only contains coins minted by the Amphaxians, the Botteatai and the Macedonians whereas no issues of Philip V and Perseus, the Roman quaestors or the three cities are present, as in most hoards. It is also worth mentioning that the type Heracles/club of the Amphaxians found in the Pella hoard, so far has been only encountered in hoards dated after the abolishment of the monarchy in 168. For these reasons, we suggest that the hoard Pella/2011 should be dated to the years 168-148 BC, that is after the battle of Pydna and before the creation of the Roman province of Macedonia.